Improvement of Oxygen‐Depolarized Cathodes in Highly Alkaline Media by Electrospinning of Poly(vinylidene fluoride) Barrier Layers. Issue 3 (6th February 2020) - Gebhard, Marcus; Tichter, Tim; Franzen, David; Paulisch, Melanie C.; Schutjajew, Konstantin; Turek, Thomas; Manke, Ingo; Roth, Christina
Abstract: Oxygen‐depolarized cathodes (ODC) were developed for chlor‐alkali electrolysis to replace the hydrogen evolution reaction (HER) by the oxygen reduction reaction (ORR) providing electrical energy savings up to 30 % under industrially relevant conditions. These electrodes consist of micro sized silver grains and polytetrafluoroethylene, forming a homogeneous electrode structure. In this work, we report on the modification of ODCs by implementing an electrospun layer of hydrophobic poly(vinylidene fluoride) (PVDF) into the ODC structure, leading to a significantly enhanced ORR performance. The modified electrodes are physically characterized by liquid flow porometry, contact angle measurements and scanning electron microscopy. Electrochemical characterization is performed by linear sweep voltammetry and chronopotentiometry. The overpotential for ORR at application near conditions could be reduced by up to 75 mV at 4 kA m −2 and 135 mV at a higher current density of 9.5 kA m −2 . Consequently, we propose that modifying ODCs by electrospinning is an effective and cost‐efficient way to further reduce the energy demand of the ORR in highly alkaline media. Abstract : Electrospinning of poly(vinylidene fluoride) into silver‐based gas diffusion electrodes is used to modify the pore system. Overpotentials for ORR are reduced by up to 75 mV at 4 kA m −2 and 135 mV at 9.5 kA m −2 under industrially relevant conditions (80 °C and 30 wt.% NaOH).